Comparation of vancomycin penetration into cerebrospinal fluid in postoperative intracranial infection and community‐acquired meningitis patients. (27th October 2018) - Cai, Yan; Zhou, Le; Wang, Huqing; Zhang, Li; Wang, Jinqiu; Zhang, Kanghuai
Summary: What is known and objective: To compare the penetration of vancomycin into cerebrospinal fluid (CSF) in patients with postoperative intracranial infection and community‐acquired meningitis, and to identify related factors influencing the penetration in these two diseases. Methods: The concentrations of vancomycin in serum and CSF were determined by enzyme amplified immunoassay, and the CSF‐to‐serum ratios were calculated. The correlation between CSF‐to‐serum ratios of vancomycin and CSF elements was analyzed. Results and discussion: In postoperative intracranial infection patients and community‐acquired meningitis patients, the vancomycin concentration in CSF was 1.90 ± 1.29 mg/L and 2.47 ± 1.15 mg/L, while the CSF‐to‐serum ratio was 0.19 ± 0.12 and 0.26 ± 0.12, respectively. There was a significant correlation between vancomycin serum concentration and bodyweight ( P <  0.05). The CSF‐to‐serum ratio in postoperative intracranial infection patients was correlated to white blood cell count in CSF. However, in community‐acquired meningitis patients, no relationship was seen with regards to CSF white blood cell count, protein or glucose. What is new and conclusion: Cerebrospinal fluid vancomycin penetration was similar in postoperative intracranial infection and community‐acquired meningitis patients. The CSF‐to‐serum ratio was only correlated to CSF white blood cell count in postoperative intracranial infection patients. Abstract : We compared the penetration of vancomycin into cerebrospinal fluid (CSF) in different patients. In postoperative intracranial infection patients, vancomycin concentration in CSF was 1.90 ± 1.29 mg/L, and the CSF‐to‐serum ratio was 0.19 ± 0.12. In community‐acquired meningitis patients, the vancomycin concentration in CSF was 2.47 ± 1.15 mg/L, and the CSF‐to‐serum ratio was 0.26 ± 0.12. The CSF‐to‐serum ratio in postoperative intracranial infection patients was correlated to CSF white blood cell count. However, in community‐acquired meningitis patients, no relationship was seen with regards to CSF white blood cell count, protein or glucose.